Apropos of the Quality Management in Higher Education - A. G. Kislov (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to introduction and implementation of quality management system in the sphere of Russian higher education. The research demanded the prehistory observation of the above processes, their legal bases analysis, as well as setting the existing practices of the state control and supervision of education in compliance with the principles of TQM (Total Quality Management). Different normative acts and documents have been reviewed concerning accreditation of higher educational establishments, and determining the state policy of quality improvement of the higher school functioning. The author emphasizes that participation of different organizations - including educational ones - in certification procedures and competitions in the quality sphere is considered voluntary according to the Russian legislation. However, for getting the state accreditation educational establishments have no other way apart from setting the internal structures responsible for students training quality. The above structures in educational establishments look rather strange and alien duplicating in their best the state control and supervision system. They appear to be quite expansive for educational establishments and demanding extra time and effort from the staff. In conclusion the author points out that the state policy forcing the quality management issues reflects the interests of certain social groups, namely those who directly participate in external supervision of higher educa- tional institutions. The research findings can be applied while correcting the educational policy of the Russian Federation, and developing the concepts of regulatory legal acts in the higher educational sphere.